2012
DOI: 10.1177/0883911512458050
|View full text |Cite
|
Sign up to set email alerts
|

Novel amelogenin-releasing hydrogel for remineralization of enamel artificial caries

Abstract: Recently, the use of recombinant full-length amelogenin protein in combination with fluoride has shown promising results in the formation of densely packed enamel-like structures. In this study, amelogenin (rP172)-releasing hydrogels containing calcium, phosphate, and fluoride were investigated for remineralization efficacy using in vitro early enamel caries models. The hydrogels were applied to artificial caries lesions on extracted human third molars, and the remineralization efficacy was tested in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…Several strategies have been proposed to replicate the enamel microstructure using chemicals, polymers, amorphous calcium phosphate (ACP) nanoparticles, dendrimers, and hydrogels. 7 New approaches to enamel remineralization have included the use of b-sheet forming peptides, 8 electrospun mats of ACP/poly (vinylpyrrolidone) nanofibers, 9 amelogenin-releasing system, 10 and casein phosphopeptide stabilized ACP. 11 Yamagishi et al have developed a dental paste that upon application on the enamel surface, under acidic pH, resulted in the formation of organized nanocrystals of apatite.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been proposed to replicate the enamel microstructure using chemicals, polymers, amorphous calcium phosphate (ACP) nanoparticles, dendrimers, and hydrogels. 7 New approaches to enamel remineralization have included the use of b-sheet forming peptides, 8 electrospun mats of ACP/poly (vinylpyrrolidone) nanofibers, 9 amelogenin-releasing system, 10 and casein phosphopeptide stabilized ACP. 11 Yamagishi et al have developed a dental paste that upon application on the enamel surface, under acidic pH, resulted in the formation of organized nanocrystals of apatite.…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al developed an agarose−amelogenin hydrogel model to regenerate the enamel-like tissue. 23 In their model, agarose was used as a releasing agent to investigate the function of amelogenin in the remineralization of early enamel caries. Although the agarose hydrogel containing calcium and phosphate without amelogenin was used as the control group, the different concentration of the inorganic ions and the different diffusion mode gave different results between our study and theirs.…”
Section: Discussionmentioning
confidence: 99%
“…CPP‐ACP serves as a supersaturation calcium and phosphate reservoir on the enamel surface and promotes the mineralization of enamel subsurface lesions . Amelogenin can stabilize the ACP and alter the aggregation to produce oriented rod‐like HAP crystals . Kim et al reported that amelogenin can promote the formation of a well‐organized enamel‐like structure when it is added to mineralization medium containing fluoride,[129b] and an amelogenin‐containing chitosan hydrogel has also been developed for enamel regeneration that can promote the assembly of enamel‐like layers on mature enamel .…”
Section: Applications Of Biomineralizationmentioning
confidence: 99%